Pengaruh Pelatihan Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Kelurahan Depok - Della Wulandari; Taat Kuspriyono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The research focuses on finding out how much influence job training and work environment have on employee performance at the Depok Village Office. The research method used is a quantitative method approach with data collection techniques using saturated samples or non probability sampling. The population in question is all employees of the Depok Village Office, totaling 30 respondents using a questionnaire in Likert scale units. In data processing for analysis using SPSS 25 software with multiple linear analysis techniques, namely instrument testing, partial and simultaneous hypothesis testing. This study found that there is a positive and significant partial and simultaneous influence between the variables of job training and work environment on the performance of Depok Village office employees.